Leader Humility and Team Innovation: Investigating the Substituting Role of Task Interdependence and the Mediating Role of Team Voice Climate - Liu, Wenxing; Mao, Jianghua; Chen, Xiao (Frontiers in Psychology, 2017)
Leadership has been found to be linked with team innovation. Based on social information processing theory and substitutes for leadership theory, this paper examines the influence of leader humility on team innovation. Results from 90 teams showed that leader humility will enhance team innovation by fostering team voice climate. Further, task interdependence substitutes the effect of leader humility on team innovation through an indirect way via team voice climate. This study discussed the theoretical and practical implementations of these observations.